Update: Splenic Artery Embolization in Blunt Abdominal Trauma - Patil, Mangaladevi S.; Goodin, Sean Z.; Findeiss, Laura K. (Seminars in Interventional Radiology, 2020)
The spleen is the most commonly injured organ after blunt abdominal trauma. Nonoperative management with splenic arterial embolization (SAE) is the current standard of care for hemodynamically stable patients. Current data favor the use of proximal and coil embolization techniques in adults, while observation is suggested in the pediatric population. In this review, the authors describe the most recent evidence informing the clinical indications, techniques, and complications for SAE.
Keywords: splenic arterial embolization; blunt splenic injury; interventional radiology; trauma